REVIEW STUDY OF FOUNDATION STRUCTURE OF BELAWAN MEDAN CRANE ELECTRIFICATION SUBSTATION BUILDING REGARDING BEARING CAPACITY AND SETTLEMENT - Pujo Priyono; Arief Alihudien; Haykal Fiendyo (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
This study aims to evaluate the foundation structure of the Crane Electrification Substation building in Belawan, Medan, against the soil bearing capacity and foundation settlement. The study was conducted through literature studies, field surveys, and structural analysis using SAP2000 software. The evaluation includes the pile bearing capacity, pile group efficiency, and analysis of single and group pile settlement. The results of the analysis show that the pile cap configuration with 8 piles provides the best performance with a total settlement of 65 mm, still within the tolerance limit as an "isolated foundation". While the configuration with 6 piles shows a settlement of 84 mm, which exceeds the limit without tie beams, but is still acceptable if the foundation is considered a "raft" system with tie beam support. This study emphasizes the importance of choosing the right foundation configuration to ensure the stability and safety of the structure.